Elaboración de harina de cabeza de camarón controlando etapa de cocción a 95ºc y secado a 75ºc - Moncada Guamán, Fanny Patricia (2011)
In the present research was elaborated flour shrimp head, controlling the cooking stage at 95ºC and dried at 75ºC, the shrimp heads underwent microbiological analysis and head meal shrimp will perform a bromatological. Obtaining the shrimp head meal was performed according to the following process: reception of the head and frozen shrimp, washing and sorting, and weighing runoff, cooked (10 to 15 minutes), runoff and weighing, drying (3 and 5 hours), heavy, grinding and packaging. For statistical analysis ANOVA was used considering 4 factors that were cooking temperatures 95 ° C, cooking times (10 and 15 min), drying temperature 75 º C and drying times (3 and 5). 4 treatments were studied over three repetitions, for a total of 16 trials and as result had more than one variable, it became a separate analysis and interpreting the results in figures, choosing the best treatment. The treatment that most closely matches the features found in the flour shrimp head commercial was made ​​with a concoction of 95 ° C for a cooking time of 15 minute and drying at 75 ° C for a drying time of 5 hours.